Sex-specific trends in the global burden and risk factors of atrial fibrillation and flutter from 1990 to 2021 - Xiaodong Peng; Jue Wang; Chen Tang; Liu He; Jiangtao Li; Shijun Xia; Xiangyi Kong; Ning Zhou; Deyong Long; Caihua Sang; Xin Du; Jianzeng Dong; et al. (Scientific Reports)
Abstract Significant sex disparities exist in the burden of atrial fibrillation and flutter. However, comprehensive and systematic analysis of its global trend by sex is scarce. The Global Burden of Disease Study 2021 was used as data source for analysis. Sex-specific prevalence, incidence, disability-adjusted life years (DALY), and mortality rates per 100,000 population from atrial fibrillation and flutter were estimated using the Bayesian meta-regression method. Temporal trends of average annual percent change (AAPC) of age-standardized and age-specific burdens across age bands were evaluated using the joinpoint model stratified by socio-demographic index (SDI). Sex differences in trends were tested using pairwise comparison. From 1990 to 2021, the global age-standardized DALY rate [from 109.93 (95% uncertainty interval, 88.5 to 134.72) to 112.05 (93.3 to 135.28), P < 0.001], age-standardized mortality rate [from 4.20 (3.65 to 4.59) to 4.44 (3.94 to 4.81), P < 0.001] for atrial fibrillation and flutter significantly increased in males, while the age-standardized incidence rate decreased from 58.0 (44.98 to 75.8) to 57.11 (46.19 to 72.14) in males (P < 0.001). Countries with low and low-middle SDI exhibited significant increases in age-standardized prevalence and incidence rates in both females and males (all P < 0.001), with a faster increase in females. Across all age bands, a faster increase in mortality was observed among males, while females under age bands of 50 years showed a higher increase in prevalence and incidence on a global scale compared to males. High systolic blood pressure was the predominant risk factor contributing to atrial fibrillation and flutter-related DALY. Notably, the impact of high body-mass index on DALY of atrial fibrillation and flutter was increasing fast over last three decades, especially in males. Although the global burden of atrial fibrillation and flutter has substantially increased, disparities exist across different sexes, age bands, and countries with different socio-demographic status.